MENTAL ILLNESS OF THE MAIN CHARACTER IN THE MOVIE DADDY’S PERFECT LITTLE GIRL DIRECTED BY CURTIS CRAWFORD - Restalia Restalia; Sulhizah Wulan Sari; Retno Dwigustini (Sean Institute, 2023)
Mental illness is a mental or psychological disorder or a health condition that affects an individual's thoughts, emotions, and behaviors in their daily life. The purpose of this research is to analyze and understand the mental illnesses experienced by the main character, to identify the types of mental illnesses and factors that contribute to the main character's mental disturbances, and how to treat the people of suffering the mental illness. In this study, the writer utilizes a qualitative descriptive research method, using images and dialogue from the film